Late city : a novel - Butler, Robert Olen (Atlantic Monthly Press, 2021)
"A visionary and deeply moving novel centered around former newspaperman Sam Cunningham as he prepares to die, Late City covers much of the early twentieth century, unfurling as a conversation between the dying man and a surprising God. As the two review Sam's life, from his childhood in the American South and his time in the French trenches during World War I to a newspaper career in Chicago in the Roaring Twenties and the decades that follow, moments of history are brought sharply into focus. Sam grows up in Louisiana with a harsh father and escapes by enlisting in the army as a sniper. The hardness his father instilled in him helps him make it out of World War I alive, but we come to realize that it also prevents him from contending with the emotional wounds of war. Back in the U.S., Sam moves to Chicago and begins a career as a newspaperman, meets his wife, and has a son, whose fate counters Sam's at almost every turn. As he contemplates his relationships-with his parents, his brothers in arms, his wife, his editor, and most importantly, his son-Sam is amazed at what he still has left to learn about himself after all these years in this heart-rending novel from the Pulitzer Prize winner"--